The role of Arabic literature arts in developing critical thinking skills among high school students from the teachers’ point of view - Alhourani, Mohammad Issa; Al Zoubi, Wesal; Al Mahamed, Ahmad Mohammad; Abouelnour, Moustafa Mohamed (Research Journal in Advanced Humanities, 2026)
At a time when educational systems are under increasing pressure to cultivate analytical, interpretive, and evaluative capacities rather than rote knowledge alone, this study addresses a highly consequential question: how can Arabic literary arts serve as an effective pedagogical pathway for developing critical thinking among secondary school students? The study responds to a clear research gap in the limited empirical attention given to the relationship between Arabic literary genres and critical thinking skills within school-based Arab educational contexts. Using a descriptive-analytical design, the researchers employed an electronic questionnaire administered to 90 Arabic language teachers in Abu Dhabi, with 35 items covering poetry, short story, literary essay, and the skills of interpretation, inference, induction, analysis, and evaluation. The study aimed to examine the contribution of Arabic literary arts to critical thinking development, measure the statistical relationship between these variables, and identify differences associated with teachers’ qualifications and experience. The findings revealed a high level of teacher awareness regarding the role of Arabic literature in enhancing critical thinking, as well as a strong statistically significant relationship between literary arts and critical thinking skills. Literary essay and short story showed comparatively stronger effects than poetry. The study recommends curriculum redesign, specialized teacher training, and further comparative and experimental research to strengthen the pedagogical integration of Arabic literature in contemporary education.